Electrocardiographic findings in 130 hospitalized neonatal calves with diarrhea and associated potassium balance disorders. (26th June 2018) - Trefz, Florian M.; Lorenz, Ingrid; Constable, Peter D.
Abstract : Background: Hyperkalemia in neonatal diarrheic calves can potentially result in serious cardiac conduction abnormalities and arrhythmias. Objectives: To document electrocardiographic (ECG) findings and the sequence of ECG changes that are associated with increasing plasma potassium concentrations ( c K + ) in a large population of neonatal diarrheic calves. Animals: One hundred and thirty neonatal diarrheic calves (age ≤21 days). Methods: Prospective observational study involving calves admitted to a veterinary teaching hospital. Results: Hyperkalemic calves ( c K + : 5.8‐10.2, blood pH: 6.55‐7.47) had significantly ( P  < .05) longer QRS durations as well as deeper S wave, higher T wave, and higher ST segment amplitudes in lead II than calves, which had both venous blood pH and c K + within the reference range. The first ECG changes in response to an increase in c K + were an increase in voltages of P, Ta, S, and T wave amplitudes. Segmented linear regression indicated that P wave amplitude decreased when c K + >6.5 mmol/L, S wave amplitude voltage decreased when c K + >7.4 mmol/L, QRS duration increased when c K + >7.8 mmol/L, J point amplitude increased when c K + >7.9 mmol/L, and ST segment angle increased when c K + >9.1 mmol/L. P wave amplitude was characterized by a second common break point at c K +  = 8.2 mmol/L, above which value the amplitude was 0. Conclusions and Clinical Importance: Hyperkalemia in neonatal diarrheic calves is associated with serious cardiac conduction abnormalities. In addition to increased S and T wave amplitude voltages, alterations of P and Ta wave amplitudes are early signs of hyperkalemia, which is consistent with the known sensitivity of atrial myocytes to increased c K + .